Seismic Risk and Vulnerability Assessment of Mid-Rise Steel Building with Soft Story Effects - Ridho Aidil Fitrah; Maulana Arif; Zev Al Jauhari (Journal of Civil Engineering and Planning (JCEP), 2026)
Soft-story irregularity is a critical form of vertical structural irregularity that significantly increases the seismic vulnerability of mid-rise steel buildings. This condition commonly occurs when the ground floor has substantially lower lateral stiffness than the upper stories due to the absence or reduction of masonry infill walls. During earthquakes, seismic demands concentrate at the weaker story, resulting in excessive inter-story drift and rapid stiffness degradation. This study evaluates the seismic performance and fragility of a seven-story steel moment-resisting frame with a soft-story configuration at the first floor. A three-dimensional numerical model was developed in ETABS and analyzed using nonlinear static pushover analysis in both principal directions. Structural properties were designed according to SNI 1729:2020, while seismic loading was based on the response spectrum specified in SNI 1726:2019 for Padang City. The resulting capacity curves were converted into the Acceleration–Displacement Response Spectrum (ADRS) format to define four performance limit states: Slight, Moderate, Extensive, and Complete Damage. Fragility curves were subsequently developed using lognormal cumulative distribution functions and HAZUS methodology to estimate the probability of exceeding each damage state under increasing spectral displacement demands. The results indicate that seismic deformation is concentrated at the soft-story level, causing significant stiffness degradation and reduced post-yield capacity. The fragility analysis reveals an increasing probability of severe damage with increasing seismic demand, confirming that soft-story irregularity substantially increases the collapse potential of mid-rise steel buildings in high-seismic regions.